Significance of adhesion molecules expression for estimation of serous ovarian cancer prognosis - Ryabtseva, O.D.; Lukianova, N.Yu.; Shmurakov, Yu.A.; Polishchuk, L.Z.; Antipova, S.V. (Experimental Oncology, 2013)
Aim: To study the adhesion molecules CD44 and E-cadherin expression in serous ovarian cancer (0C) and their relationship with clinicopathological peculiarities of tumor process and prognosis. Materials and Methods: The studywas performed on QC samples from 72 patients with serous DC of stages I-III. Expression of CD44 and E-cadherin in tumor samples was evaluated with the use ofimmunohistochemical analysis. Results: Immunohistochemical analysis has revealed that in 58.3% of 0C patients CD44 expres- sion was detected in more than 10% of cells with average level of 30.0+-5.6%. E-cadherin expressionwas present in 47.2% of tumors, and 12.2+-3.6% cells were immunopositive. CD44 and E-cadherin expression depends on degree of cytomorphological malig- nancy and cell differentiation. A reverse correlation between CD44 and E-cadherin expression in primary serous 0C (r=-0.38, p<0.05) has been found. Increased CD44 expression (mean index) was not observed in peritoneal metastases compared to primary tumors, but analysis of individual indexes showed increase of CD44 expression in 46.6% 0C patients with metastases. The dependence between overall survival of 0C patients and the molecular phenotype of tumor cells, in particular, poor prognosis for CC patients with CD44(+)/E-cadherin(-) and CD44(+)/budding(+) tumor cells phenotype, has been revealed. Conclusion: The results of morphological and immunohistochemical analysis has shown the incnease of adhesive features of serous ovarian cancer cells what may be signiﬁcant for estimation of ovarian cancer aggressiveness and development of metastatic process. Key Words: serous ovarian cancer, CD44, E-cadherin, immunohistochemical analysis, morphology, budding, malignancy, prognosis.